Regulon analysis identifies protective FXR and CREB5 in proximal tubules in early diabetic kidney disease - Wanting Shi; Weibo Le; Qiaoli Tang; Shaolin Shi; Jingsong Shi (BMC Nephrology, 2023)
Abstract Diabetic kidney disease (DKD) is the most common complication of diabetes mellitus and a leading cause of kidney failure worldwide. Despite its prevalence, the mechanisms underlying early kidney damage in DKD remain poorly understood. In this study, we used single nucleus RNA-seq to construct gene regulatory networks (GRNs) in the kidney cortex of patients with early DKD. By comparing these networks with those of healthy controls, we identify cell type-specific changes in genetic regulation associated with diabetic status. The regulon activities of FXR (NR1H4) and CREB5 were found to be upregulated in kidney proximal convoluted tubule epithelial cells (PCTs), which were validated using immunofluorescence staining in kidney biopsies from DKD patients. In vitro experiments using cultured HK2 cells showed that FXR and CREB5 protected cells from apoptosis and epithelial–mesenchymal transition. Our findings suggest that FXR and CREB5 may be promising targets for early intervention in patients with DKD.